2014
DOI: 10.1088/0004-637x/795/1/62
|View full text |Cite
|
Sign up to set email alerts
|

Changing Ionization Conditions in SDSS Galaxies With Active Galactic Nuclei as a Function of Environment From Pairs to Clusters

Abstract: We study how active galactic nucleus (AGN) activity changes across environments from galaxy pairs to clusters using 143,843 galaxies with z < 0.2 from the Sloan Digital Sky Survey. Using a refined technique, we apply a continuous measure of AGN activity, characteristic of the ionization state of the narrow-line emitting gas. Changes in key emission-line ratios ([N ii] λ6548/Hα, [O iii] λ5007/Hβ) between different samples allow us to disentangle different environmental effects while removing contamination. We c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 76 publications
(132 reference statements)
1
30
0
Order By: Relevance
“…Much of the observational evidence for these effects is derived from studies of galaxies which exhibit strong morphological disturbances and/or galaxies which have a close companion. It is now well established that, on average, these galaxies have enhanced star formation rates (Barton, Geller, & Kenyon 2000;Ellison et al 2008a;Freedman Woods et al 2010;Scudder et al 2012;Patton et al 2013;Davies et al 2015 Plauchu- Frayn & Coziol 2010a,b;Ellison et al 2010;Casteels et al 2014), lower nuclear metallicities (Kewley, Geller, & Barton 2006;Ellison et al 2008a;Michel-Dansac et al 2008;Kewley et al 2010;Scudder et al 2012;Ellison et al 2013) and increased AGN activity (Alonso et al 2007;Silverman et al 2011;Liu, Shen, & Strauss 2012;Ellison et al 2013;Khabiboulline et al 2014;Satyapal et al 2014) compared with relatively isolated and/or undisturbed galaxies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the observational evidence for these effects is derived from studies of galaxies which exhibit strong morphological disturbances and/or galaxies which have a close companion. It is now well established that, on average, these galaxies have enhanced star formation rates (Barton, Geller, & Kenyon 2000;Ellison et al 2008a;Freedman Woods et al 2010;Scudder et al 2012;Patton et al 2013;Davies et al 2015 Plauchu- Frayn & Coziol 2010a,b;Ellison et al 2010;Casteels et al 2014), lower nuclear metallicities (Kewley, Geller, & Barton 2006;Ellison et al 2008a;Michel-Dansac et al 2008;Kewley et al 2010;Scudder et al 2012;Ellison et al 2013) and increased AGN activity (Alonso et al 2007;Silverman et al 2011;Liu, Shen, & Strauss 2012;Ellison et al 2013;Khabiboulline et al 2014;Satyapal et al 2014) compared with relatively isolated and/or undisturbed galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…There are already a number of galaxy pair studies which report differences in galaxy properties at pair separations of 50-100 kpc Patton et al 2011;Scudder et al 2012;Casteels et al 2013;Ellison et al 2013;Khabiboulline et al 2014;Satyapal et al 2014) and some which report differences beyond 100 kpc (Park et al 2007;Li et al 2008;Robaina et al 2009;Park & Choi 2009;Koss et al 2010;Patton et al 2013). However, there are a number of challenges that arise when attempting to extend existing techniques out to such wide separations.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are now many studies that have shown that interactions over a wide range of mass ratios can 1 trigger AGN that are selected variously in the optical (e.g. Alonso et al 2007;Ellison et al 2011Ellison et al , 2013Kaviraj 2014;Khabiboulline et al 2014), mid-IR (Satyapal et al 2014;Shao et al 2015) and X-ray (Koss et al 2010(Koss et al , 2012Silverman et al 2011;Lackner et al 2014). For radio selected AGN, there is evidence to support a connection between mergers and both HERGs and the highest luminosity radio-loud AGN (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This pressure is able to strip gas from galaxies (ram pressure stripping), which may cause tails of stripped gas to form behind the galaxy as it moves in the cluster, as has been observed for galaxies in the Virgo cluster (e.g., Kenney et al 2004;Crowl et al 2005;Chung et al 2007). Ram pressure stripping leads to a decreased prevalence of radio-mode AGN activity in the centers of clusters (e.g., Ellison et al 2011;Ehlert et al 2014;Khabiboulline et al 2014), since the ram pressure has depleted the gas supply of these central galaxies. However, models and hydrodynamical simulations show that lower ram pressures can compress the gas in the galaxy, and may induce star formation (e.g., Fujita & Nagashima 1999;Kronberger et al 2008;Kapferer et al 2009;Tonnesen & Bryan 2009;Bekki 2014), which is also supported by observations (e.g., ).…”
Section: Comparison With Theoretical Predictionsmentioning
confidence: 95%